PELATIHAN PEMBUATAN PAVING BLOCK TEXTURE SEAMLESS BAGI PEMUDA DESA MESJID PEUNTEUT KOTA LHOKSEUMAWE - Zairipan Jaya; Edi Majuar; Amir Fauzi; Muhammad Reza; Mirza Fahmi (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2023)
Youth dropping out of school in Mesjid Peunteut Village, Blang Mangat District, Lhokseumawe City as a partner village were still less productive and have an impact on low income levels. In fact, they have never received training from any party for entrepreneurial activities and have the expertise to create certain products, especially in the field of civil engineering. This training aimed to provide knowledge and skills to out-of-school youth in order to provide them with the expertise to make seamless texture paving block products that are easy to market so as to generate a steady income. The number of participants involved in the activity were 20 people, consisted of 8 women and 12 men with an age range of 20 - 25 years. Partners acquired theoretical knowledge, technical skills in making paving block texture seamless manual products, production management and product marketing. The offline method was used for theoretical debriefing activities combined with presentation techniques in class and hands-on practice in civil engineering workshops. The results of the training obtained an average value of theoretical understanding of 88.1 and technical understanding of 95. This showed partners have acquired theoretical and technical knowledge to plan mix compositions, manufacture products manually, arrange production and marketing costs. Thus, it becomes a job field for youth who drop out of school to get a steady income.